Development of slow food awareness scale and examination of the effectiveness of slow food training: The effectiveness of education in slow food... - Ozgen, Leyla; Pektaş, Sami (Progress in Nutrition, 2019)
Aim: In this research, it is aimed to develop a valid and reliable scale which can reveal the awareness of the students about slow food. Moreover, the aim of the study was to provide the students with training in slow food and to determine the effectiveness of the training given. Materials and methods: In the scale development phase of the research, descriptive model was used. On the other hand, experimental model was used to determine the effectiveness of the training. Study group: The study group consists of 210 students in Abant Izzet Baysal University, Gastronomy and Culinary Arts Department and 185 students in the Cookery Program of Mengen Vocational Higher School in 2016-2017 Academic Year in Bolu, Turkey. Results and discussion: In the scale development stage, exploratory factor analysis was performed according to the answers obtained from the study group and it was determined that the scale consisted of 22 items collected in three dimensions. The items in the scale explained 57.98% of the total variance. In addition to this, factor load values of scale items ranged between 0.55 and 0.79. In addition to the scale development study, 185 students were also included in the scale; pretest and posttest were applied. Slow food training was given to the students by using methods and tools such as power point presentation, question-answer, group discussion, demonstration, brain storming, dramas, games and storytelling. Conclusions and suggestions: As a result of the education of the students, it was found that there was a positive increase in the level of knowledge of both girls and boys.